An Approach to the Research Methodology for a Doctoral Study - Lee, Kwee-Heng; Wan Abdullah, Nik Rosnah; Raja Ariffin, Raja Noriza (Journal of Governance and Development (JGD), 2023)
This paper discusses the research methodology employed in a doctoral study entitled, “Impacts of legislative controls on private hospitals in Malaysia”. The research methodology encompasses the general design to the research process, from the theoretical framework to the collection and the analysis of data. The paper commences with the discussion on the methodological approaches as to whether a positivist or naturalistic framework or a combination of mixed method approach is most appropriate to be utilised in this study. This methodological decision making process led to the choice of a qualitative study. It then describes the methods for data collection, the analysis and the coding process from the key informants’ interviews, observations and discourses which formed the core of the research methodology. Several emergent themes which are interlinked have been identified and crystallized as the empirical findings that provide answers to the research questions and objectives of the study.